Mycobacterium abscessus and kansasii successfully treated with inhaled amikacin: Case report - Ramirez, Percy C. (2025)
Introduction: Pulmonary infections by nontuberculous mycobacteria (NTM) represent a serious clinical problem because they produce progressive, severe and difficult to treat pictures. Case report: We present two patients without immunosuppressive comorbidity with pulmonary infection by Mycobacterium abscessus and Mycobacterium kansasii, with clinical and radiographic improvement after receiving inhalation amikacin. The use of this drug added to standard therapy allowed a favorable evolution due to its high concentration in the alveolar tissue in infection by non-tuberculous mycobacteria. Discussion: Initial therapy to treat NTM infections based on a macrolide, ethambutol and rifampicin is often not sufficient. Inhalation amikacin is proposed as rescue therapy due to its potent antimicrobial activity, achieving a high concentration and a longer time in lung tissue with less toxic effects. Conclusion: A favorable clinical response was evidenced with the combined treatment with inhaled amikacin.